Hoop dreams on wheels [ disability and the competitive wheelchair athlete - Berger, Ronald J. (Contemporary sociological perspectives, 2009)
"Hoop Dreams on Wheels is written in an accessible story-telling style, as it is intended to be read by a general audience as well as by students in college courses on disability, sports, the body, and social problems. The main component of the book, the life histories of the players, will be especially appealing to students, who will find these accounts useful as a way to develop their sociological imagination, that is, an understanding of the interrelationship between biography and history in society and the ways in which personal troubles are related to public issues. By linking personal stories to collective narratives, the life histories reveal the world of ordinary people's "problematic lived experience," to quote Norman Denzin, and show how society "speaks itself" through the lives of individuals. Additionally, the book is of interest to scholars in the sociology of disability, sociology of sports, sociology of the body, life-history researchers, and professionals in the fields of therapeutic recreation and rehabilitative counseling."--BOOK JACKET.